Padronização de uma PCR para o diagnóstico da leucose enzoótica bovina e sequenciamento parcial do gene ENV - Marcelo Fernandes Camargos (2001)
The Enzootic Bovine Leukosis (EBL) is viral disease responsible for the development of lymphosarcomas in cattle. The polymerase chain reaction (PCR) using the primers BLV1 and BLV2, was used with success for amplification and detection of a part of the envelope gene (env) in samples of bovine leucocytes from EBL - seropositive and EBL - seronegative animals. The sensitivity of PCR was determines by the accomplishment of PCR in tubes containing serial dilutions of DNA extracted from a sample isolated from an infected animal. The load of 120 pg of DNA as template for PCR gave positive results. The specificity of PCR was determined by enzymatic restriction with Bam HI and by sequence analysis of three samples. The results obtained with PCR and agar gel-immunodiffusion (AGID) were compared, with 73,8% agreement between the tests.